Evaluasi Implementasi Kebijakan Standar Pelayanan Minimal Bidang Kesehatan di Kabupaten Gunungkidul - KHOZIN, MOHAMMAD (Jurnal Studi Pemerintahan, 2010)
Minimum service standard policy applied since 2002 are based on the Minimum Service Standard(SPM) arranged in circular Minister of Home Affairs No. 100/756/OTDA/2002, then set up furtherin Government Regulation No. 65 2005 edge various obstacles both at internal level bureaucracy northe external environment. This research tries to answer how far the implementation of the policy ofMinimum Service Standards could improve the quality of health service?. The public service is anactivity that is performed by a person or a group of people with a materially factors through the system,specific procedures and methods in order to attempt to satisfy the interests of others in accordance withhis authority. The research method used is a qualitative method by combining data analysis of primarydan data secondary. Standard service for a minimum of Gunungkidul Regency field can beaccomplished with either. This can be seen from a comparison of the data from the indicator one yearsections that have been compiled. But of the many indicators of the performance of service sections thathave been set, still there are some indicators that are not obvious targeting.